Preparation, Characterization, and Mechanism of SMS Titanium–Manganese Nanocomposite for Antimony Removal from Water - Yannan Lv; Wenqing Wen; Shenrui Han; Kaixin Li; Ziyu Fu; Fansong Mu; Meng Luo (Separations)
This study investigates the synthesis of SMS-Ti-Mn (SMS-Ti-Mn stands for spent mushroom substrate activated carbon-Ti-Mn) nanocomposites and their application in removing the heavy metal antimony from water. In the process of antimony mining and smelting, the concentration of antimony in the waste residue can still reach as high as 80.5 mg/L. In addition, the soil in the electronic waste dismantling area is severely contaminated with antimony. In short, antimony enters the environment in various ways from mining, smelting, and manufacturing to the final waste process and continuously migrates in different environmental media, increasing the environmental exposure risk of antimony pollution. Single-factor experiments and response surface methodology were employed to determine the optimal conditions, including the adsorption time, pH, and solid–liquid ratio. Material characterization was performed to understand the role of nano-metals, and adsorption kinetics were analyzed using the quasi-first-order kinetic model. The research results revealed that the optimal conditions for antimony removal were an adsorption time of 40 min, a pH of 4, and a solid–liquid ratio of 2:1 (mg/mL). Under these conditions, the nanocomposites showed an adsorption capacity of 10.502 mg/g, which was 5.8 times higher than that of iron coagulants, 11 times higher than that of manganese-modified activated carbon, and 1.7 times higher than that of iron–manganese sludge adsorbents. Characterization revealed enhanced functional groups (carbonyl, Ti=O, Mn=O), contributing to improved adsorption. Kinetic analysis indicated physical adsorption as the dominant mechanism, and the regression model accurately predicted the adsorption capacity. SMS-Ti-Mn nanocomposites offer a promising strategy for treating antimony-contaminated water, with strong potential for practical applications in water treatment. They can decompose naturally after use, reduce secondary pollution, and promote ecological balance. Secondly, agricultural waste treated with heavy metal removal can be used as a fertilizer and soil amendment to improve soil quality and promote sustainable agricultural development.